2006
DOI: 10.1021/la052796r
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Resistant Polymer Coatings on Silicon Oxide by Surface-Initiated Atom Transfer Radical Polymerization

Abstract: The modification of silicon oxide with poly(ethylene glycol) to effectively eliminate protein adsorption has proven to be technically challenging. In this paper, we demonstrate that surface-initiated atom transfer radical polymerization (SI-ATRP) of oligo(ethylene glycol) methyl methacrylate (OEGMA) successfully produces polymer coatings on silicon oxide that have excellent protein resistance in a biological milieu. The level of serum adsorption on these coatings is below the detection limit of ellipsometry. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
232
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 219 publications
(242 citation statements)
references
References 36 publications
10
232
0
Order By: Relevance
“…Adsorption of trichlorosilanes on a variety of oxide surfaces is irreversible, but traces of water lead to the deposition of ill-defined multilayers through formation of siloxane linkages ͑Si-O-Si͒. 84,85 Use of a monochlorosilane avoids this complication, Fig. 2͑B͒.…”
Section: A Self-assembled Monolayersmentioning
confidence: 99%
See 2 more Smart Citations
“…Adsorption of trichlorosilanes on a variety of oxide surfaces is irreversible, but traces of water lead to the deposition of ill-defined multilayers through formation of siloxane linkages ͑Si-O-Si͒. 84,85 Use of a monochlorosilane avoids this complication, Fig. 2͑B͒.…”
Section: A Self-assembled Monolayersmentioning
confidence: 99%
“…SAMs of adsorbates bearing a bromoisobutyryl group at the termini have been used to initiate ATRP of oligo͑eth-ylene glycol͒ methacrylate ͑OEGMA͒ monomer. 70,85,165 Similar to poly͑ethylene glycol͒ and SAMs of EG n on gold, the poly͑OEGMA͒ polymer brushes prevent protein adsorption. Extensive studies of the SI-ATRP of OEGMA polymer brushes on silicon and gold substrates indicate that the length 6.…”
Section: B Polymer Brushes In the Design Of Biomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose poly(oligo(ethylene glycol) methyl ether methacrylate) [poly(OEGMA)] for in situ polymer growth because we had previously shown that poly(OEGMA) brushes grown on a planar surface confer exceptional protein and cell resistance to the surface of diverse materials (25)(26)(27), and we hypothesized that the corollary to protein resistance on surfaces is a long circulation half-life when the same polymer is grown from the surface of a protein. Furthermore, poly(OEGMA) can be synthesized by atom transfer radical polymerization (ATRP)-a living radical polymerization methodology-in aqueous medium (25)(26)(27) with good control of the polymer chain length (28), attributes that we believed would be invaluable for the growth of stoichiometric and functionally active polymer conjugates from the surface of a protein.…”
mentioning
confidence: 99%
“…Furthermore, poly(OEGMA) can be synthesized by atom transfer radical polymerization (ATRP)-a living radical polymerization methodology-in aqueous medium (25)(26)(27) with good control of the polymer chain length (28), attributes that we believed would be invaluable for the growth of stoichiometric and functionally active polymer conjugates from the surface of a protein. In addition, poly(OEGMA) is likely to be biodegradable due to the enzyme-degradable and hydrolyzable ester linker (Fig.…”
mentioning
confidence: 99%